The Role of Parents and Teachers in the Development of Children's Digital Literacy Interests from the Perspective of Behaviorist Learning Theory - Abdurrauf, Abdurrauf (Maliki Interdisciplinary Journal, 2025)
The aim of this research is to increase children's interest in digital literacy through the role of parents and teachers. The development of children's digital literacy interests is greatly influenced by interactions with their surrounding environment. In the context of digital literacy, parents and teachers can act as models and facilitators who introduce literacy to children. This research was written using the library research method where data and information were collected from relevant theoretical sources. This research involved a literature review of previously published journal articles, books, and related research reports. The results of this research are strategies that parents and teachers can apply to increase children's interest in digital literacy in terms of behaviorist learning theory. Among the strategies that parents can use are providing stimulus, positive reinforcement, creating a supportive and comfortable environment and encouraging collaboration with other family members. Likewise, teachers make it possible to provide positive reinforcement in the form of rewards and implement audio-visual based learning.